RESPONSIVITAS DINAS PUPR TERHADAP ARTIKULASI KEPENTINGAN MASYARAKAT TENTANG JALAN RUSAK DI KOTA PEKANBARU TAHUN 2022 - Simarmata, Irani Debora; Susanto, Agus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
Damaged roads have an impact on people's mobility, such as disrupting road access and causing accidents. This impact has resulted in complaints from the public and hopes for corrective action from the Pekanbaru City Public Works and Spatial Planning Department. This research aims to determine the responsiveness of the Pekanbaru City PUPR Service to the articulation of community interests regarding damaged roads in Pekanbaru City in the form of road repair actions based on articulated community complaints. The research location is in Pekanbaru City, precisely at the Pekanbaru City Public Works and Spatial Planning Department. This research uses the theory of responsiveness proposed by Tangkilisan, there are 2 indicators, namely the bureaucracy's ability to prepare an agenda to handle service user complaints and the bureaucracy's ability to respond to complaints from service users. This research uses a descriptive qualitative approach. Data Collection Techniques through interviews and documentation. The results of this research show that the PUPR Service's ability to prepare an agenda for handling service user complaints through the proposed road maintenance work program listed in the 2022 Pekanbaru City PUPR Service Work Plan (RenJa), PUPR has responded to complaints from service users, namely the community, through the realization of the work plan with consider service user complaints that have been articulated, although not all service user complaints can be responded to and receive remedial efforts from the Pekanbaru City PUPR Service Keywords: Response, Complaints, Community, Road, Damaged